Household proximity to water and nontuberculous mycobacteria in children with cystic fibrosis. Issue 3 (30th January 2017) - Bouso, Jennifer M.; Burns, James J.; Amin, Raid; Livingston, Floyd R.; Elidemir, Okan
Summary: Background: Nontuberculous mycobacteria (NTM) have a particular affinity for patients with cystic fibrosis (CF). Recent studies suggest a possible relationship between acquiring NTM and the level of environmental water in a given area. We sought to determine if there is an association between household proximity to water and NTM in children with CF. Materials and Methods: An IRB‐approved retrospective chart review was completed on 150 children with CF in Florida. Inclusion criteria required regular follow‐up, at least two acid‐fast bacilli cultures, and a consistent home address over a 3‐year period. The distance from each patient's home to the nearest body of water was measured using ArcMap®, a Geographic Information System, and the mean distance to water for NTM‐positive and NTM‐negative groups were compared. A stepwise backwards logistic regression was used to evaluate for predictors of NTM‐positivity. Results: Of the 150 CF patients, 65 met inclusion criteria and 21 (32.3%) tested positive for NTM. Comparison of the mean distance to water for NTM‐positive versus NTM‐negative groups revealed a cutoff of 500 meters. On the logistic regression, CF patients who lived within 500 meters of water were 9.4 times more likely to acquire NTM ( P  = 0.013). Other significant predictors included a history of Aspergillus fumigatus (OR 7.9, P  = 0.011) and recent history of Pseudomonas aeruginosa (OR 2.5, P  = 0.007). Conclusions: In the regions studied, children with CF who live closer to water are more likely to acquire nontuberculous mycobacteria. Future studies in other geographic areas are needed to determine if these results are generalizable.Pediatr Pulmonol. 2017;52:324–330. © 2016 Wiley Periodicals, Inc.